BETWEEN RECOGNITION AND EXCLUSION: Indigenous Peoples’ Rights in Asia's Development Policies - Komari, Komari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This article critically examines the paradox of legal recognition and structural exclusion of indigenous peoples in Asia, with a focus on the Philippines, Nepal, and Indonesia. While many Asian states have adopted progressive legal instruments to recognize indigenous rights—often aligning with international standards such as ILO Convention No. 169 and UNDRIP—implementation remains fragmented, conditional, and subordinate to dominant development paradigms. Drawing on a critical policy analysis of legal texts, governance frameworks, and regional case studies, the paper argues that recognition, in the absence of structural transformation, functions as a tool of managed inclusion that obscures ongoing dispossession. Development policies driven by extractive economies, centralized authority, and technocratic rationalities continue to marginalize indigenous territories and knowledge systems. The article calls for a reconfiguration of recognition as a decolonial and rights-based practice that centers indigenous sovereignty, co-governance, and epistemic justice in shaping inclusive futures.